The Functions of BET Proteins in Gene Transcription of Biology and Diseases - Cheung, Ka Lung; Kim, Claudia; Zhou, Ming-Ming (Frontiers in Molecular Biosciences, 2021)
The BET (bromodomain and extra-terminal domain) family proteins, consisting of BRD2, BRD3, BRD4 and testis-specific BRDT, are widely acknowledged as major transcriptional regulators in biology, owing to their two characteristic tandem bromodomains (BrDs) binding to lysine-acetylated histones and transcription factors to recruit transcription factors and coactivators to target gene sites, and to activate RNA polymerase II machinery for transcriptional elongation. Pharmacological inhibition of BET proteins with BrD inhibitors has been shown as a promising therapeutic strategy for the treatment of many human diseases including cancer and inflammatory disorders. The recent advances in bromodomain protein biology have further uncovered the complex and versatile functions of BET proteins in the regulation of gene expression in chromatin. In this Review, we highlight our current understanding of BET proteins’ functions in mediating protein-protein interactions required for chromatin-templated gene transcription and splicing, chromatin remodeling, DNA replication, and DNA damage repair. We further discuss the latest development of BET bromodomain inhibitors as emerging epigenetic therapies for cancer and inflammatory disorders.